Potential of organ donation from deceased donors: study from a public sector hospital in India. (24th June 2014) - Kumar, Vivek; Ahlawat, Ravinder; Gupta, Anil K.; Sharma, Rakesh K.; Minz, Mukut; Sakhuja, Vinay; Jha, Vivekanand
Summary Deceased donor organ programme is still in infancy in India. Assessing deceased donation potential and identifying barriers to its utilization are required to meet needs of patients with organ failure. Over a 6‐month period, we identified and followed all presumed brainstem dead patients secondary to brain damage. All patients requiring mechanical ventilation with no signs of respiratory activity and dilated, fixed and nonreacting pupils were presumed to be brainstem dead. All events from suspicion of brainstem death (BSD) to declaration of BSD, approach for organ donation, recovery and transplants were recorded. Subjects were classified as possible, potential and effective donors, and barriers to donation were identified at each step. We identified 80 presumed brainstem dead patients over the study period. The mean age of this population was 35.9 years, and 67.5% were males. When formally asked for consent for organ donation (n = 49), 41 patients' relatives refused. The conversion rate was only 8.2%. The number of possible, potential and effective donors per million population per year were 127, 115.7 and 9.5, respectively. The poor conversion rate of 8.2% suggests a huge potential for improvement. Family refusal in majority of cases reflects poor knowledge and thus warrants interventions at community level.